2017
DOI: 10.1016/j.fluid.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Measurement, correlation and COSMO-SAC prediction of liquid-liquid equilibrium for the ternary systems, mesityl oxide + o-, m-, p-cresol + water, at 333.2K and 353.2 K

Abstract: In this work, liquid-liquid equilibrium (LLE) data for the ternary systems, mesityl oxide + o-, m-, p-cresol + water, were determined at 333.2 K and 353.2 K under 101 kPa. The high distribution coefficient and selectivity calculated by the experimental tie-line data indicate excellent efficiency for mesityl oxide extracting cresols from aqueous solutions. The NRTL and UNIQUAC models were used to correlate the experimental LLE data, with root mean square deviations (RMSDs) below 2.1% and 1.5%, respectively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…The subscripts i , j , and k are defined as the compounds, phase type, and determined data points, respectively. The detailed process of both equations has been described in many previous articles , and is not repeated here. The interaction energy parameters correlated by both thermodynamic models are included in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subscripts i , j , and k are defined as the compounds, phase type, and determined data points, respectively. The detailed process of both equations has been described in many previous articles , and is not repeated here. The interaction energy parameters correlated by both thermodynamic models are included in Table .…”
Section: Resultsmentioning
confidence: 99%
“…These wastewaters contain a large amount of toxic phenolic substances. The low-concentration phenolic wastewater discharged without further treatment has serious impact on the health of human beings, animals, and plants. , Many researchers studied to extract phenol, cresol, and dihydroxybenzene from coal gasification wastewater, but there have been few papers to focus on solvent extraction of dimethylphenol. Dimethylphenol is one of the various harmful phenols in coal gasification wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid–liquid equilibrium (LLE) data of ternary and binary systems were usually correlated using nonrandom two-liquid (NRTL) and universal quasichemical (UNIQUAC) activity coefficient models in order to determine the binary interaction parameters used in process simulation. There are many available references reporting the results of solubility measurements in aqueous solutions since accurate solubility data are important for product and process design. Many organic solvents have been reported to extract methylphenol from wastewater including ketones, ethers, aliphatic hydrocarbons, and aromatic hydrocarbons . However, most of those references focused on temperatures below 323.15 K. Methyl tert -butyl ketone (MTBK) showed good physicochemical properties such as relatively low boiling point, little solubility in water, and high partition coefficient and selectivity for the treatment of phenolic wastewater, ,, which are a benefit for the extraction and solvents recovery process.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al studied the impact of carbon chains including C–C or CC bonds on the polarity of a molecule and revealed that the polarity of a molecule containing a CC bond is higher than that containing a C–C bond. In addition, MO tends to represent a high distribution coefficient toward catechol. However, MO is an α, β-unsaturated carbonyl compound and shows higher reactivity than ordinary solvents of liquid extraction fields. Then, it is necessary to determine the limitations of using MO in liquid–liquid equilibrium studies.…”
Section: Introductionmentioning
confidence: 99%